(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
Multiparticulates are discrete particles that make up a multiple unit system. Although pellets have been used in the pharmaceutical industry for more than four decades, with the advent of controlled release technology, that the full impact of the inherent advantages of pellets over single unit dosage forms have been realized, not only has focused on refining and optimizing existing pelletization techniques, but also focused on the development of novel approaches and procedures for manufacturing of pellets. The present review outlines the manufacturing and evaluation of pellets. The manufacturing techniques include layering, cryopelletization, freeze pelletization, extrusion spheronization and hot melt extrusion have been discussed. Characterization of pellets is discussed with reference to the particle size distribution, surface area, porosity, density, hardness, friability and tensile strength of pellets.